Vehicular delay-tolerant networks – an overview - Soares, V.N.G.J. (2009)
Vehicular Delay-Tolerant Networks (VDTNs) are a networking paradigm based on concepts of Delay-Tolerant Networks (DTNs) and Opportunistic Networks. Opportunistic contacts, intermittent connectivity, frequent network partition, long propagation delays and no contemporaneous end-to-end paths characterize VDTNs. VDTNs have been proposed to interconnect developing communities, or to implement disaster recovery networks when all other networks fail. Other possible application scenarios for these networks include traffic monitoring, accident warnings, advertisements, or data gathering applications. The diversity of these network environments introduces challenging issues related to the architecture, protocols design, interoperability, security, management, and stability of VDTNs. This communication starts with the presentation of VDTNs architecture. In the sequence, it focuses on problems that arise from low network node density and missed transmission opportunities, vehicle movement models, constrained network resources on routing strategies, and scheduling and drop policies.